Design of a Low-cost and Compact Radiometer for Spectral Acquisition of Vegetation and Bare Soil - Nawel Zemaili, Mokhtaria; Benabadji, Noureddine; Hassini, Abdelatif (Bulletin of Electrical Engineering and Informatics, 2016)
We describe, in this article, the design of a low-cost and compact radiometer with five analog channels for spectral acquisition: four in the visible (blue, green, red and panchromatic) and one channel in the near-infrared. This small embedded system is based on an 8-bit microcontroller for automatic data acquisition, calibrating, storing and serial link processing with a compatible PC, through a C++ application software provided to handle and deal with the mass of data collected and stored in an EEPROM. The acquisition of spectral reflectance measurements of an object for different wavelengths allows the construction of a characteristic curve, named spectral signature of the object. The study of the spectral signatures of different types of surfaces such as water, bare ground or vegetation allows their identification in remote sensing image processing, and Â consequently, facilitates the interpretation of this kind of data, as, for instance, the AVHRR data of the HRPT images acquired and freely distributed by the satellite NOAA.